In silico screening of chalcones and their derivatives as potential inhibitors of spike proteins and ACE2 enzymes for SARS-CoV-2 treatment - Thi Thu Hang Ta; Bao Kim Nguyen; Thi Hong Khanh Do; Thanh Tung Bui (Vietnam Journal of Science, Technology and Engineering, 2022)
The COVID-19 pandemic causing acute respiratory syndrome is a significant public health problem. Drugs that can treat this disease are currently a high priority. The SARS-CoV-2 spike protein and human ACE2 enzyme receptor, which both play important roles in virus entry into the host cell, are promising therapeutic targets for inhibiting viral infection. This research evaluates the potential of chalcone compounds to inhibit the spike proteins and ACE2 enzymes through molecular docking in silico approaches. Based on the ChemFaces database, we collected 92 chalcone compounds. These compounds were further docked to target the active sites of spike protein and human ACE2. After comparing the binding energies of the 92 compounds to artemisinin, ribavirin, and lopinavir, which have inhibitory activity to these protein targets of SARS-CoV-2, we chose 20 out of the 92 compounds that had a higher ability to inhibit the protein targets than the reference inhibitors. Next, five phytochemical compounds with the best binding energy were selected, which included flavanomarein, sarcandrone B, sarcandrone A, calyxin H, and sieboldin. Then, Lipinski’s 5 rule was used to evaluate the druglike properties of these compounds. Predictive ADME/tox filtering tests were also applied to the top docked compounds. The results suggest that sarcandrone B has good pharmacokinetic properties, which should be further explored as an anti-SARS-CoV-2. To confirm these findings, experimental studies are recommended.